Nanoscale Microstructural and Chemical Analysis of SiO2–Zn1−xAlxO Nanocomposites: Towards a Better Understanding of Si and Al Substitution in ZnO. Issue 12 (11th September 2015) - Gilbert, Matthieu; Byl, Celine; Berardan, David; Gloter, Alexandre; Dragoe, Nita; Vurpillot, François
Abstract : In this study, we report on the microstructure of SiO2 ‐coated Al‐doped ZnO nanoparticles densified by spark plasma sintering(SPS), using a multiscale approach. Our observations show that it is possible to successfully prepare dense pellets while keeping the nanostructure with well‐defined Si‐rich grain boundaries. Although a very limited partial solubility of Si in the ZnO matrix has been observed, Si is mostly concentrated at the grain boundaries. More surprisingly, we evidenced some areas with nanoscale inhomogeneity of the Al concentration, which can locally strongly exceed the average composition of the matrix. It could explain the apparent discrepancy observed in the literature between the simultaneous presence of ZnAl2 O4 in Al‐doped ZnO, which should be the signature of the doping level exceeding the solubility limit, and the concentration of carriers that still depends on the nominal Al concentration in ZnO even in the presence of ZnAl2 O4 .